University Mathematics Classroom Teaching Quality Assessment Based on Core Competencies Using the DEMATEL Approach and Single-Valued Neutrosophic Hypersoft Sets - Jingjing Qiao (Neutrosophic Sets and Systems)
This study proposes a multi-criteria decision-making (MCDM) approach to evaluate the quality of University Mathematics Classroom Teaching based on core competencies. The MCDM approach is applied within the framework of the neutrosophic set to address vague and uncertain data. Unlike the hypersoft set, which handles multiple disjoint attribute-valued sets corresponding to various characteristics, the soft set operates with a single set of attributes. This study introduces the concept of Single-Valued Neutrosophic Hypersoft Expert Sets (SVNS), which integrate single-valued neutrosophic sets and hypersoft expert sets. Eight criteria were employed to construct the pairwise comparison matrix. The Decision-Making Trial and Evaluation Laboratory (DEMATEL) method was utilized to analyze the interrelationships among the criteria within the SVNS and hypersoft set frameworks. The results indicate that Conceptual Understanding utilizes the highest impact among the criteria.